Functionalisation of multiwalled carbon nanotubes with melamine phosphate and their influence on morphology, thermal stability, flame retardancy and mechanical properties of ABS. (7th February 2021) - Ding, Yonghong; Guo, Liang; Yang, Jinghong; Li, Yongchao; Cao, Zheng; Lu, Guangwei; Zhao, Zhiyuan
ABSTRACT: Multiwalled carbon nanotubes (MWCNTs) were carboxylated by nitric acid oxidation/plasma pretreatment, and melamine phosphate (MP) was grafted onto the surface of MWCNTs to obtain functionalised MWCNTs-MP. The modified MWCNTs were characterised by FT-IR, Raman spectroscopy, XRD, 1 H-NMR, TEM, SEM and TGA. The results proved the successful preparation of MWCNTs-MP. The acrylonitrile–butadiene–styrene copolymer (ABS) composites were prepared by melt blending with MWCNTs-MP and characterised using TGA, microscale combustion calorimeter, limiting oxygen index (LOI), SEM and tests to record mechanical properties. The addition of 1% MWCNTs-MP to ABS improved its thermal stability, reduced combustion parameters and increased its LOI value by 27.8%. This is attributed to the MP grafted onto the surface of the MWCNTs. During combustion, this forms a char layer that acts as a heat transfer barrier. The enhanced mechanical properties of the composite were attributed to the improved dispersion of the modified MWCNTs-MP in ABS.